2008
DOI: 10.1108/09544780810842910
|View full text |Cite
|
Sign up to set email alerts
|

Integration of CRM and QFD

Abstract: Purpose -The purpose of this paper is to propose an integrated model of quality function deployment (QFD) and customer relationship management (CRM) for design and delivery processes. Design/methodology/approach -After the literature review, the elements of a CRM business cycle were integrated with different phases in QFD. The proposed model was further developed, based on customer participation in the design and delivery of products/services, as a major stage in CRM in three cases: customer participation in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Suppose an efficient CRM leads to the bottom-line profit for the organization [24]. CRM systems help organizations acquire customer knowledge and produce continuously [25].…”
Section: Crm Performance and Customer Participationmentioning
confidence: 99%
“…Suppose an efficient CRM leads to the bottom-line profit for the organization [24]. CRM systems help organizations acquire customer knowledge and produce continuously [25].…”
Section: Crm Performance and Customer Participationmentioning
confidence: 99%
“…Moreover, marketing practitioners and researchers have increasingly recognized that customer co-creation has positive effects on firm performance by increasing productivity and decreasing costs Ramaswamy, 2000, 2004). The improvement in firm performance arises from various sources: cost-minimization caused by customers serving as ad hoc employees (Lovelock and Young, 1979;Bitner and Brown, 2008), greater repurchases and referrals (Cermak et al, 1994;Shahin and Nikneshan, 2008), higher consumer well-being (Guo et al, 2013;Mende and Van Doorn, 2015), better brand image (Woisetschläger et al, 2008;Shamim et al, 2016), faster response to service failures (Dong and Sivakumar, 2017) and improved service/product development and innovation (Tether and Tajar, 2008;Grissemann and Stokburger-Sauer, 2012). From the customer perspective, customers can accrue economic value through the co-creation process as they benefit from cost reductions and discounts (Prahalad and Ramaswamy, 2004).…”
Section: The Outcomes Of Customer Co-creationmentioning
confidence: 99%
“…Ding (2009) has successfully applied QFD to identify problems in the shipping system at the port of Kaohsiung, Taiwan, with the help of customers' suggestions, he was able to solve the problem at the port. The results of the research by Shahin and Nikneshan (2008) which used the concept of customer relationship management in QFD found that the main problem in the delivery of goods lies in the quality of human resources. Meanwhile Lam and Lai (2014) used QFD to develop sustainable shipping.…”
Section: Qfd Implementation In Delivery Service Productsmentioning
confidence: 99%